Efektivitas Model Pembelajaran IMPROVE Ditinjau dari Kemampuan Adversity Quotient - Padrul Jana; Apendika Nugrahayuningtyas (Didaktik Matematika, 2019)
This research aimed to examine the effectiveness of IMPROVE learning model in the learning of mathematics in terms of adversity quotient ability of Grade 8 students in one of the public junior high school in Yogyakarta. This type of research was a quasi-experiment by using the Nonequivalent Posts-Only Control Group Design. The variables in this study included the independent variables of IMPROVE learning model and adversity quotient ability; and the dependent variable was student learning outcomes. The population in this research were all Grade 8 classes in one of the public junior high school in Yogyakarta. The sampling was done by purposive sampling system and selected one class was chosen as an experimental class and another class as a control class. The instrument used in this research was posttest and a questionnaire of adversity quotient that has been tested. The classification of students adversity quotient is Climber, Champer, and Quitter. The results of this study showed that IMPROVE learning model was more effective than direct learning model, in terms of adversity quotient ability of grade 8 students in one of the public junior high school in Yogyakarta. This research contributes to the development of studies on aspects that make the IMPROVE method more effective on adversity quotient ability.